Highlighting Energy Policies and Strategies for the Residential Sector in Malaysia - Bekhet, Hussain Ali; Ivy-Yap, Lee Lian (International Journal of Energy Economics and Policy, 2014)
Energy is an important catalyst for development. Malaysia is very fortunate to be endowed with oil reserves. However, these reserves are finite and not renewable. Being cognizant of this, the Malaysian government had implemented various energy policies and strategies to manage and safeguard its oil reserves for better energy security as well as to promote prudent use of energy. This paper aims to highlight the electricity sector in Malaysia and the various policies and strategies implemented thus far. By reviewing the existing energy policies and strategies as well as their implications, this paper suggests prospective policy and strategy options towards achieving better energy efficiency and emission reduction in the residential sector. The trends of electricity consumption and underlying factors influencing the growth of electricity consumption are also discussed. Keywords: residential electricity consumption; energy policies; renewable energy; energy efficiency, JEL Classifications: C54; Q48; Q54; R41